'I don't think I ever had food poisoning'. A practice-based approach to understanding foodborne disease that originates in the home. (1st February 2015) - Wills, Wendy J.; Meah, Angela; Dickinson, Angela M.; Short, Frances
Highlights: Current theories of practice were used in this study. This is a new approach to explore domestic kitchen practices and foodborne disease. Foodwork is entangled within broader practices and extends beyond the kitchen. Food safety is subsumed within everyday life in the kitchen. New ways of thinking about risk, vulnerability and food safety are suggested. Abstract: Food stored, prepared, cooked and eaten at home contributes to foodborne disease which, globally, presents a significant public health burden. The aim of the study reported here was to investigate, analyse and interpret domestic kitchen practices in order to provide fresh insight about how the domestic setting might influence food safety. Using current theories of practice meant the research, which drew on qualitative and ethnographic methods, could investigate people and material things in the domestic kitchen setting whilst taking account of people's actions, values, experiences and beliefs. Data from 20 UK households revealed the extent to which kitchens are used for a range of non-food related activities and the ways that foodwork extends beyond the boundaries of the kitchen. The youngest children, the oldest adults and the family pets all had agency in the kitchen, which has implications for preventing foodborne disease. What was observed, filmed and photographed was not a single practice but a series of entangled encounters and actions embedded and repeated, often inconsistently, by the individuals involved. Households derived logics and principles about foodwork that represented rules of thumb about 'how things are done' that included using the senses and experiential knowledge when judging whether food is safe to eat. Overall, food safety was subsumed within the practice of 'being' a household and living everyday life in the kitchen. Current theories of practice are an effective way of understanding foodborne disease and offer a novel approach to exploring food safety in the home.